A voltage-emulated peak current controlled buck converter for automotive applications with in-built over-current protection. (May 2022) - Deo, Anupama; Maity, Ashis; Patra, Amit
Abstract: This paper proposes a voltage-emulated peak-current-sensing scheme for a DC–DC buck converter operating in a wide supply voltage of 4–36 V for automotive applications. In the conventional scheme, the peak current is detected by sensing the high-side switch current using an op-amp based feedback mechanism, where limited bandwidth of sensing loop restricts the sensing speed. Furthermore, initial ringing in the switching node introduces a significant error in the peak-current-sensing. The proposed peak-current-sensing scheme adopts a current-comparison based approach for eliminating the op-amp. The error voltage emulates the reference current for current comparison and dynamically adjusts its value with load. Therefore, the peak current detection is faster and more accurate. The efficacy of the proposed scheme is extended to implement over-current protection for the converter with an in-built maximum current limiter which restricts the maximum sense-FET current. The circuit is designed in TSMC 0 . 18 μ m BCD process. Post-layout simulation results are presented to validate the effectiveness of the proposed peak-current-sensing scheme.